Regulation of angiotensin converting enzyme and angiotensin II type 1 receptor by 17beta-estradiol in female rats: Implications following experimental myocardial infarction - Dean, Stephanie A (University of Ottawa (Canada), 2005)
The present studies tested the hypothesis that 17beta-estradiol (E2) downregulates ACE and AT1R in several tissues important to cardiovascular regulation, including the brain and heart, and that this downregulation attenuates the progression of LV dysfunction following myocardial infarction (MI). In Experiment 1, female Wistar rats were randomized into one of four groups: (1) sham-ovariectomized (OVX); (2) OVX+vehicle (veh); (3) OVX+E2 replacement at physiological levels and (4) OVX+high E2. Five weeks following OVX, ACE and ATIR were increased 15-90% in the heart, several cardiovascular nuclei of the brain, kidney, abdominal aorta, adrenal and lung. These increases were prevented in all cases by E2 replacement at physiological levels and in most cases reversed to decreases by high E2. In Experiment 2, age-matched female Wistar rats underwent 1 of 3 treatments: no surgery (ovary-intact), OVX+veh treatment for two weeks, or OVX+high E2 treatment for two weeks. (Abstract shortened by UMI.)
Keywords: Health Sciences, Pharmacology.